RECONSTRUCTING THE CONCEPT OF SUMMARY PROOF WITHIN THE LEGAL FRAMEWORK OF SMALL CLAIMS PROCEDURES - Kresna Ramadhan Wijaya; Rachmi Sulistyarini; M. Natsir Asnawi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This research analyzes the legal reasoning (ratio legis) behind the qualification of "simple" in the current Small Claims Court regulation and formulates a reconstruction of that meaning. Currently, Supreme Court Regulation (PERMA) No. 4 of 2019 defines "simple" based on quantitative-administrative limits, such as a maximum claim value of IDR 500 million and domicile constraints. This normative legal research uses statute, conceptual, and philosophical approaches. The results indicate that the current paradigm is pragmatic-economic, aimed at judicial efficiency and Ease of Doing Business (EoDB) rankings, but often neglects substantive justice. This study proposes a reconstruction by shifting the paradigm from Quantitative Simplicity to Evidentiary Simplicity. Under this new framework, a case is categorized as "simple" based on its evidentiary characteristics (clear-cut case/liquid debt) rather than its nominal value, ensuring broader access to justice for cases with high economic value but low evidentiary complexity.